(untitled) (Research, Society and Development, 2021)
To adapt to social changes and remain competitive, organizations were driven to invest in the Human Resources (HR) sector. The role of Human Resource Business Partner (HRBP) has become an option for organizations searching for greater agility in HR processes and bringing this sector closer to the company’s business strategy. Through the experience report, this work aims to analyze the beginning of the professional trajectory of an HRBP in a technology startup, listing the developed skills and the difficulties faced. The lack of seniority and training to fill the HRBP role were some of the main factors that made it difficult to work in this position. However, a senior BP follow-up, carrying out oriented activities, and gaining the trust of the teams allowed a more assertive performance. The opportunity to act and develop important skills such as strategic and systemic vision, analytical and business knowledge, communication, and leadership training were important to highlight. Due to the HRBP role prominent in recent years, and the lack of national academic about it, this report wants to contribute to other professionals who aim to migrate to this area and encourage future research.